'The track is never the same': The fluidity of geographic terminology and conceptualisation of space among Ewenki. Issue 3 (May 2020) - Mamontova, Nadezhda; Klyachko, Elena; Thornton, Thomas F
Abstract : This paper analyses landscape terminology in Ewenki, one of the Tungusic languages spoken by indigenous hunters and reindeer herders in Siberia, using examples of three key conceptual categories: 'mountain' / elevation, flat terrain and river terms. Based on linguistic data obtained from 14 Ewenki communities across a large, diverse geographic terrain, semantic analysis suggests that the system of landscape terminology in Ewenki is heterogeneous with significant variations in the meaning of landscape terms and categories one can observe across the dialect continuum. The uniqueness of the Ewenki landscape terminology lies in the fact that the same term can reference completely different landscape features, remaining semantically linked to all of these objects. This variation in meaning is especially evident in terms for 'plains', as this type of landscape is particularly prone to transformations in their Siberia homeland. These changes reflect the Ewenki people's unique nomadic engagement with the land, their flexible adaptation to new ecosystems and their perception of landscapes as being constantly changing or fluid. The relationships between the meanings of the terms across the dialect continuum are considered within ethnophysiography and ontology of the geographic domain.